How volleyball coaches perceive the match analysis - Vicente, J. P.; Sampalo, A. J.; Mesquita, I.; Mota, M. P. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
It is well known that world top Volleyball coaches are using match analysis to enhance game performance and, ultimately, sport success (1). In fact, the available literature suggests that match analysis is a key factor in preparing teams for the games (2,3). However, all studies are focused on the game and no study is focused on coaches. Therefore, the aim of the present study was to identify the Volleyball coaches` perceived importance regarding the match analysis process. Methods 40 Volleyball coaches (20 coaches of 1st and 2nd male seniors division; 10coaches of 1st female seniors division and 10 coaches of national teams) answered an adapted questionnaire (4) about their perception on the match analysis process. Data was analysed with descriptive frequencies and percentages of all questions and to compare groups, a qui-square (61539;2) and a One-way ANOVA with Scheffe multiple comparisons was performed. The level of significance was established in 5%. Results/Conclusion Results allowed to suggest that: 1) all coaches use the match analysis to study the opponent team and to improve his own team; 2) the coaches observe all the opponent`s games; 3) bearing in mind the information transmitted to his players, all the coaches are very specific during the exercises, games-trainings, and meetings prior to games in order to correct errors, using video images of competitions disputed by the opponents; 4) all the coaches attribute great importance to the definition of offensive strategies to overcome the opponents; 5) 92,5% of the coaches give the information with more than 48h in advance to the players; 6) the coaches tendencies goes through an identification of the positive and negative aspects of the opponent team and by the definition of the offensive strategies to use to exceed them; 7) 82,5% of the coaches use an instrument of observation supported on his own model of training and competition; 8) 73,7% of the coach`s carries out match analysis through manual register from direct observation of both teams; 9) 60% of the coaches present 2 elements as responsible by the department of match analysis. In what concerns to match analysis, our results highlight the need to improve qualified staff formation recurring to new available software. As this would allow more valid and reliable information to coaches`, we believe that could give an important contribute to the strategy for overcoming the opponents.